The Relationship between the Digital Leadership of School Administrators and the Innovative Organization of the School under the Bangkok Metropolitan Administration - Singamoo, Patchareeporn; Lapcharoen, Supawadee (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2025)
This research aimed to examine 1. the level of digital leadership of school administrators under the Bangkok Metropolitan Administration 2. the level of innovative organization of the school under the Bangkok Metropolitan Administration and 3. The relationship between the digital leadership of administrators and the level of innovative organization of school under the Bangkok Metropolitan Administration. The sample group is 370 teachers on duty in educational institutions affiliated to Bangkok Metropolitan Government in the academic year 2024. Research Findings 1. The level of digital leadership of school administrators under the Bangkok Metropolitan Administration is at the highest level 2. The level of innovative organization of the school under the Bangkok Metropolitan Administration is at the highest level and 3) There is a relationship between the digital leadership of administrators and the level of innovative organization of the school under the Bangkok Metropolitan Administration, with a statistical significance level of .01.